Penetrating blast injury involving maxilla to infratemporal fossa: An unusual wounding mechanism following heavy tractor wheel explosion. Issue 3 (May 2016) - Malachovský, Igor; Janík, Martin; Straka, Lubomír; Novomeský, František
Abstract: Although most significant maxillofacial injuries are the result of blunt trauma, solitary penetrating facial injuries with retained foreign bodies occur, and can be particularly difficult to manage, since multiple vital structures are concentrated in a relatively small anatomic area. When penetrating facial injuries occur, they are usually caused by low-velocity gunshots, falls, criminal assaults, occupational, or traffic accidents. Occasionally, however, maxillofacial surgeons may be encountered with penetrating facial injuries caused by unusual etiologies. Blast injuries to the face owing to tire or metal rim fragments explosion provide a specific example of such a traumatic event. In addition to initial pressure wave which can produce severe overpressure barotrauma, an exploding wheel tire assemblies or objects in the close tire vicinity may act as a high-speed secondary projectile that can produce serious or even fatal penetrating injuries to the person facing the wheel. This report documents solitary heavy tractor tire blast-induced penetrating injury caused by metallic blunt object (combination pliers) firmly impacted in the right maxillary sinus. The unusual wounding mechanism of this injury is highlighted and the principles in the management of such a case are emphasized.